Pengembangan WebSocket pada Aplikasi e-Auction Berbasis Web dengan Menggunakan Metode Agile pada Perusahaan Balai Lelang - Maulana Ardhiansyah; Shelby Dwi Anugrah (Teknik Informatika Universitas Pamulang, 2022)
In this era, the mechanism for the development of buying and selling products or services is very rapid, especially in the field of auctions. Advances in information and communication technology such as the internet and websites are very important to use, one of which is in the implementation of auctions. Through this process, prospective participants and bidders will register to take part in the event and have the right to be the winner of the auction, it's just that until now all the processes are still using the conventional system. As a solution to overcome this problem, the author conducted a study that aims to transform a conventional system into a modern system by developing a web-based e-Auction application. In its development, the author uses agile methods to approach so that the resulting application is in accordance with user needs. This application uses the PHP programming language (Hypertext Preprocessor), the program framework uses CodeIgniter, Socket.io to create e-Auction features and MySQL as a database to store data. The results of this study are in the form of a web-based e-Auction application that results in accurate and more computerized data management in conducting auctions, and can minimize data loss.